Frontline Experiences of a Practice Redesign to Improve Self-Management of Obesity in Safety Net Clinics - AuYoung, Mona (J Ambul Care Manage, 2015)
BACKGROUND: Teamlets of physicians and medical assistants may help improve obesity management in primary care settings. We aimed to understand the barriers and facilitators of implementing a teamlet approach to managing obesity in three safety net clinics. METHODS: Key stakeholder interviews (n=21) were conducted both during early implementation of practice change and six months later; Patient surveys (n=393) examined obese patient activation and health status. RESULTS: Insufficient program resources and limited patient engagement due to external factors were implementation barriers, despite fairly high patient activation. DISCUSSION: Staff members need time and resources to execute new responsibilities to support obesity management in safety net settings. Due to high turnover, multiple supporters may improve sustainability.